The Effect of Moringa Leaf and Water Hyacinth Root Filtrate on Seed Germination and Growth of Expired Red Chili (Capsicum annuum L.) Plants - Shafitri, Nadya Rahmadhani; Rahayu, Yuni Sri (LenteraBio : Berkala Ilmiah Biologi, 2025)
This study aims to describe the effects of filtrate types and seed expiration periods on the germination and growth of expired red chili pepper (Capsicum annuum L.). The research used a Completely Randomized Design (CRD) for germination and a Randomized Block Design (RBD) for growth, with two treatment factors: filtrate types (6 types) and seed expiration periods (1, 2, and 3 months). Each germination treatment used 200 seeds in 2 replicates, totaling 36 experimental units. For growth, each treatment had 5 replicates with one plant per replicate, totaling 90 experimental units. The observed parameters included germination parameters (seed growth rate, vigor index, germination uniformity, and germination rate) and growth parameters (plant height, number of leaves, root length, and fresh weight). Data were analyzed using two-way ANOVA followed by Duncan’s test. Treatment F (100 ml water hyacinth root filtrate + 0 ml moringa leaf filtrate) showed the most optimal results for germination, while treatments B (100 ml moringa leaf filtrate + 0 ml water hyacinth root filtrate) and C (75 ml moringa leaf filtrate + 25 ml water hyacinth root filtrate) showed the most optimal results for growth. Seeds with a 1-month expiration period showed the highest results for all parameters.